Cardiac CT - Dewey, Marc; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
Computed tomography of the heart has become a highly accurate diagnostic modality that is attracting increasing attention. This extensively illustrated book aims to assist the reader in integrating cardiac CT into daily clinical practice, while also reviewing its current technical status and applications. Clear guidance is provided on the performance and interpretation of imaging using the latest technology, which offers greater coverage, better spatial resolution, and faster imaging. The specific features of scanners from all four main vendors, including those that have only recently become available, are presented. Among the wide range of applications and issues to be discussed are coronary artery bypass grafts, stents, plaques, and anomalies, cardiac valves, congenital and acquired heart disease, and radiation exposure. Upcoming clinical uses of cardiac CT, such as plaque imaging and functional assessment, are also explored.
Technical and personnel requirements -- Anatomy -- CT in the context of cardiovascular diagnosis and management -- Cardiac CT in clinical practice -- Clinical indications -- Patient preparation -- Physics background and radiation exposure -- Examination and reconstruction -- Toshiba Aquilion 64 and Aquilion ONE -- Siemens Somatom Sensation and definition -- Philips Brilliance 64 and Ict -- General Electric Light Speed VCT and Discovery CT750HD -- Reading and reporting -- Coronary artery bypass grafts -- Coronary artery stents -- Coronary artery plaques -- Cardiac function -- Cardiac valves -- Coronary artery anomalies -- Congenital and acquired heart disease -- Typical clinical examples -- Results of clinical studies -- Outlook.
Electronic reproduction.
Keywords: Heart -- Tomography; Cardiovascular diseases -- Radiography; Diagnostic techniques, Cardiovascular; Tomography scanners, X-Ray computed; Tomography, X-Ray computed -- Methods; Heart -- Diseases -- Diagnosis; Heart -- Imaging; Medicine; Electronic books